Social Entrepreneurs’ Musings: A Premise for Value Creation - Ali, Muhammad; Qureshi, Muhammad Imran (International Journal of Engineering and Technology, 2018)
The purpose of this study is to identify the gap left behind by conventional medical practices which is filled by non-allopathic medicine and the motivation behind initiation of this step by founders/creators of such businesses. Semi structured interviews are conducted from non-allopathic service provider organizations and interview data is analyzed to detect themes behind their motivations and ultimate objective of conducting such a business in a non-favorable market. Identification of issues is synonymous with founder’s prior experience in said context, market opportunity identification, financial survival and suggestion of a viable solution to address the issue on sustainable grounds is the objective. The classification of social enterprise businesses is dependent on creation of social value primarily and financial value on secondary level through provision of alternative solutions. This study takes a new step in identifying market gaps on the basis of interchangeable financial to social value objectives.